DIETARY FIBER AND ANTIOXIDANT ACTIVITY OF GLUTEN-FREE COOKIES WITH COFFEE CHERRY FLOUR ADDITION - Damat, Damat; Anggriani, Rista; Setyobudi, Roy Hendroko; Soni, Peeyush (Coffee Science - ISSN 1984-3909, 2019)
Coffee husk and coffee pulp are by-product of coffee fruit and bean processing, can be considered as potential functional ingredients for food production as coffee cherry flour (CCF). The CCF contains a lot of carbohydrates, proteins, caffeine, tannins, and polyphenols. In this study, CCF was combined with modified arrowroot starch (MAS) and modified cassava flour (MOCAF) into cookies and improvement on the physical, chemical, and nutraceutical properties of the cookies were studied. The cookies consisted of 20 % of MOCAF and 80 % mixed of modified arrowroot starch and CCF in five levels (80 %:0 %; 75 %:5 %; 70 %:10 %; 65 %:15 %; 60 %:20 %) and objective physical, chemical, and nutraceutical properties of the cookies were assessed. The results showed that the total dietary fiber content was enhanced from 11.69 % to 19.48 % with a high proportion of 20 % CCF. The cookies added with CCF displayed enhanced antioxidant activity. Acceptable cookies were obtained by adding 5 % CCF. Thus, the results implied that cookies with CCF addition obtained dietary fiber enriched cookies with improved antioxidant activity.